KEABSAHAN ALAT BUKTI ELEKTRONIK DALAM UNDANG-UNDANG NO. 11 TAHON 2008 - Bunadi Hidayat (Masalah-Masalah Hukum, 2011)
Transactions in cyber crime and activities of illegal business, such as; fraud, piracy, interception, cyber porn, cyber sex, face books, traffickings, gambling etc, hve been phenomenon and threatening the people in overseas. Facing these cyber crimes, the Government has implemented Constitution Number 11 the year 2008, concerning Information and Electrical Transaction. Based on the judicial considerations of this constitution, some of electrical media are legal evidences by off which values are correspondent to traditional evidences. This statement can be found in : Article 1 point (2 ), Article 31 point ( 1 ) /TE Constitution; JunctoArticle 12 verse ( 1 and 2 ), Article 15 verse ( 1) Constitution Number 8 the year 1997, concerning on Document of Company; Juncto Article 184 Criminal Justice System ; Article 1320 Civil Code or Burgerfijk Wetboek ( B. W) ; Juncto Article 164 Rechtsreglement Voor De Buitengewesten ( R.Bg) ; JunctoArticle 45 Herziene lndonesische Reglement ( H.I.R ). Hence, any documents and information using electrical media, can be classified as the legal evidences in trial court.